In Search of Priestly Witness: A Barthian Intervention in the Chinese Church–State Relationship in a Neoliberal Age - Li, Quan (A journal of church and state, 2025)
This article suggests a theological proposal for envisioning the relationship between the church and state in the context of the Chinese neoliberal regime. It consists of three interrelated tasks. First, I argue that the rise of a neoliberal state has shaped the Chinese political landscape over the past four decades and constrained the collective responses of the Chinese house churches in their cooperative and negotiating strategies. Then, I examine two recent theological announcements by the church leaders and evaluate their strengths and weaknesses in addressing the principles of church-state relations. This critical analysis is followed by a rediscovery of Barth’s theological politics of priestly witness, which has laid the Christological foundation for the integrity of faith communities and shed light on their primary concerns and actions towards the Chinese neoliberal state. In this way, I seek to contribute to the ongoing discussion of Chinese political theology by offering a nascent analysis of the political system encountered by the house churches and reclaiming Barth’s theological legacy for these churches in public witness.